ASESMEN KOMPETENSI MINIMUM SOSIALISASI DAN PENDAMPINGAN PENYUSUNAN SOAL BAGI GURU SEKOLAH DASAR - Vianty, Machdalena; Amrullah, Amrullah; Maharani, Dwi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Reading literacy and mathematical literacy are important for students because they help them develop logical-systematic skills, reasoning skills using the concepts and knowledge they have learned, as well as skills to understand, sort and use information critically. Both literacy skills are part of the Minimum Competence Assessment or Asesmen Kompetensi Minimum (AKM) which forms the National Assessment. Although all elementary conduct AKM, it is only for the Year 5 students. Therefore, this community service was aimed to provide all the teachers of SD Persit Kartika II-3 Palembang with the information about AKM and guide them to practice writing AKM questions. The results of this community service showed that all participants had a better picture about what AKM was and they were also able to write or compose questions that were in accordance with the characteristics of AKM. The activity ended with the submission of a collection of questions that the participants had written to the school.